Pruning and additional fertilizer applications affect morphophysiological characters and flavonoid content of winged bean - Tustiyani, Isna; Melati, Maya; Aziz, Sandra Arifin; Syukur, Muhammad; Faridah, Didah Nur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Excessive leaf production in winged bean may delay the flowering time and reduces the yield, therefore, shoot pruning and additional fertilizer were applied in order to improve yield. The research was carried out at Leuwikopo Experimental Station, IPB University, Bogor from January to July 2022. The study used a randomized complete block design with 2 factors and three replications. The first factor was three types of shoot pruning, namely without shoot pruning, shoot pruning at 15, and 30 cm height. Pruning was conducted at 7 weeks after transplanting (WAT). The second factor was four doses of fertilizers (0, 6.25, 12.5, and 18.75 g of NPK (16-16-16) per plant). The additional fertilizer was given every two weeks from 7 until 15 WAT. The variables observed were the morphophysiological characters, shoot auxin levels, plant nutrient levels, pod yield, pod number, and pod flavonoid content. The results showed that plant’s biomass increased with additional fertilizer, lower relative growth rate and higher auxin content was from 15 cm pruning. The interaction of two factors affected flowering time and flavonoid content. Shoot pruning and 6.25 g NPK delayed flowering by 0.7-1 day. The highest flavonoid content was found in the plant without pruning and additional fertilizer. Plant yields were not significantly affected by treatments. Keywords: auxin; flavonoid content; flowering time; leaf nutrient; young pods